2005
DOI: 10.1542/peds.2004-2479
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Parental Readiness to Make Changes for Overweight Children

Abstract: ABSTRACT. Objective. The prevalence of childhood obesity is increasing in the United States. However, it has been difficult to help children successfully lose weight and maintain weight loss. Parental involvement in this effort is important. Currently, little is known about parents' readiness to make behavior changes to help their children lose weight. The objective of this study was to describe demographic factors and parental perceptions associated with parents' readiness to make weight-reducing lifestyle ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
260
4
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(292 citation statements)
references
References 28 publications
15
260
4
13
Order By: Relevance
“…8 Parents' recognition that their children's weight was in excess and presented a health risk was found to be key to parental readiness to encourage lifestyle changes in their children. 15 However, although more than 25% of Canadian children aged 2-17 are overweight or obese, only 9% of parents believe their child to be overweight or obese. 41 Results of this study suggest that children and youth exposed to overweight/obesity in their immediate environments in which people they see on a daily basis, such as parents and schoolmates, are overweight or obese may develop false perceptions of what constitutes an appropriate weight status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Parents' recognition that their children's weight was in excess and presented a health risk was found to be key to parental readiness to encourage lifestyle changes in their children. 15 However, although more than 25% of Canadian children aged 2-17 are overweight or obese, only 9% of parents believe their child to be overweight or obese. 41 Results of this study suggest that children and youth exposed to overweight/obesity in their immediate environments in which people they see on a daily basis, such as parents and schoolmates, are overweight or obese may develop false perceptions of what constitutes an appropriate weight status.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important that parents have an accurate perception of their child's body weight, as parental awareness is key to behavioral change in children and adolescents. 8,15,41 Previous research has shown that one's weight status perception develops early in life, reportedly as early as age 9. 42,43 Our finding that variation in misperception was attributable to schoolmate and parent BMI in children as young as age 9 further highlights the need for obesity prevention early in the life course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, active participation in these strategies depends partly on the ability of parents to recognize when their child is overweight. Several studies (2)(3)(4)(5)(6)(7)(8)(9)(10) have examined how parents perceive their child's weight status. Their perception of weight status is then usually compared with actual weight status categorized using BMI.…”
mentioning
confidence: 99%
“…Their perception of weight status is then usually compared with actual weight status categorized using BMI. These studies have reported that the prevalence of overweight, calculated from parental perception, is significantly lower than the prevalence of overweight categorized using BMI (2)(3)(4)(5)(6)(7)(8)(9)(10) . The reasons for underestimating weight status are varied and include: parents' belief that their child will 'grow into their weight' and is therefore not an immediate problem (4,9) ; the belief that a bigger child may be healthier than one who is thin (4) ; and the concern that highlighting overweight may encourage the development of eating disorders (3,4) .…”
mentioning
confidence: 99%